Quality comparability assessment of a SARS-CoV-2-neutralizing antibody across transient, mini-pool-derived and single-clone CHO cells. Issue 1 (1st January 2022) - Xu, Gangling; Yu, Chuanfei; Wang, Wenbo; Fu, Cexiong; Liu, Hongchuan; Zhu, Yanping; Li, Yuan; Liu, Chunyu; Fu, Zhihao; Wu, Gang; Li, Meng; Guo, Sha; et al.
ABSTRACT: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has triggered a serious public health crisis worldwide, and considering the novelty of the disease, preventative and therapeutic measures alike are urgently needed. To accelerate such efforts, the development of JS016, a neutralizing monoclonal antibody directed against the SARS-CoV-2 spike protein, was expedited from a typical 12- to 18-month period to a 4-month period. During this process, transient Chinese hamster ovary cell lines are used to support preclinical, investigational new drug-enabling toxicology research, and early Chemistry, Manufacturing and Controls development; mini-pool materials to supply Phase 1 clinical trials; and a single-clone working cell bank for late-stage and pivotal clinical trials were successively adopted. Moreover, key process performance and product quality investigations using a series of orthogonal and state-of-the-art techniques were conducted to demonstrate the comparability of products manufactured using these three processes, and the results indicated that, despite observed variations in process performance, the primary and high-order structures, purity and impurity profiles, biological and immunological functions, and degradation behaviors under stress conditions were largely comparable. The study suggests that, in particular situations, this strategy can be adopted to accelerate the development of therapeutic biopharmaceuticals and their access to patients.